PENERAPAN PERATURAN DAERAH KABUPATEN BADUNG NOMOR 3 TAHUN 1992 TERKAIT DENGAN LARANGAN MENDIRIKAN BANGUNAN PAAD DAERAH JALUR HIJAU DI DESA CANGGU - Dwaranika, Ni Kade Bunga; Arthani, Ni Luh Gede Yogi (Jurnal Hukum Mahasiswa, 2024)
The unauthorized construction in the green belt of Canggu Village, particularly along Padang Lenjong Subak Liplip Street, violates Article 3 of the 1992 regulation prohibiting the establishment of illegal structures in green belt areas. This study aims to evaluate the enforcement of Regulation No. 3 of 1992 regarding this prohibition in Canggu Village and identify challenges in its implementation. Despite rapid tourism sector growth in the region, there are negative impacts, such as the reduction of Green Open Space (Ruang Terbuka Hijau or RTH) in Badung Regency. Regulations pertaining to green belts in Badung Regency are governed by Regional Regulation No. 3 of 1992. This article employs an empirical method with a legislative and factual approach to analyze the implementation of these regulations. It is hoped that the Badung Regency government will take decisive actions to enforce green belt rules and maintain a balance between tourism development and environmental preservation.